PERLINDUNGAN HUKUM TERHADAP HAK PEREMPUAN SEBAGAI KORBAN KEKERASAN DALAM RUMAH TANGGA (KAJIAN PERSPEKTIF HAK ASASI MANUSIA) - Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2016)
Issues of justice and human rights in relation to the enforcement of the law is not a simple job to be realized. Violence against women in general is a serious problem experienced by many women in Indonesia, because this issue is like a small pyramid on top but large at the bottom because it's hard to get an exact figure because of the